Dosimetric comparison of helical tomotherapy using different techniques, simultaneous integrated boost and sequential boost for craniospinal irradiation: A single institution experience - Bongkot Jia-Mahasap (2018)
© 2017 Cambridge University Press. Purpose Craniospinal irradiation (CSI) has become an important and challenging radiation technique for radiation oncologists. Helical tomotherapy (HT) seems to have dosimetric advantage for CSI compared with other radiation modalities. The purpose of this study was to compare dosimetric data between two different HT plans; simultaneous integrated boost (SIB) and sequential boost (Sq). Method Twelve previously treated CSI contoured datasets by SIB technique were replanned. Dosimetric comparative parameters of targets were conformity index (CI) and homogeneity index (HI). For organ at risk (OARs), the mean dose of parallel organs, D2% of serial organs and whole body integral dose (ID) were also investigated. Result SIB plan significantly provided more conformed dose to CSI and tumour boost while resulting in a similar CI in spinal boost region compared with Sq plan. The HI showed no differences between two plans. Radiation exposure to serial organs and ID were also significantly lower in SIB plan. Conclusion CSI treatment using HT, SIB technique was feasible and had more target coverage while minimising the radiation dose to healthy tissues.